2019
DOI: 10.1038/s41598-019-44062-0
|View full text |Cite
|
Sign up to set email alerts
|

Co-overexpression of AVP1 and OsSIZ1 in Arabidopsis substantially enhances plant tolerance to drought, salt, and heat stresses

Abstract: Abiotic stresses such as water deficit, salt, and heat are major environmental factors that negatively affect plant growth, development, and productivity. Previous studies showed that overexpression of the Arabidopsis vacuolar H + -pyrophosphatase gene AVP1 increases salt and water deficit stress tolerance and overexpression of the rice SUMO E3 ligase gene OsSIZ1 improves heat and water deficit stress tolerance in transgenic plants. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…In addition, HSPs are known as stress-responsive proteins, as their concentration increases rapidly in plant cells in response to environmental stresses [79,80]. Currently, many research groups are investigating the mechanisms of action or function of HSPs in plants under various abiotic stress-causing conditions such as drought, salt, cold, heat, and even herbicides [81][82][83][84][85][86]. As expected, we determined that HSP transcript levels are higher under combined drought and herbicide stresses.…”
Section: Memory Of Gene Expression and Sensitivity Reduction In E Cosupporting
confidence: 60%
“…In addition, HSPs are known as stress-responsive proteins, as their concentration increases rapidly in plant cells in response to environmental stresses [79,80]. Currently, many research groups are investigating the mechanisms of action or function of HSPs in plants under various abiotic stress-causing conditions such as drought, salt, cold, heat, and even herbicides [81][82][83][84][85][86]. As expected, we determined that HSP transcript levels are higher under combined drought and herbicide stresses.…”
Section: Memory Of Gene Expression and Sensitivity Reduction In E Cosupporting
confidence: 60%
“…The Arabidopsis vacuolar H + ‐pyrophosphatase gene AVP1 and the rice SUMO E3 ligase gene OsSIZ1 were fused to Cauliflower mosaic virus 35S promoter and a maize ubiquitin promoter, respectively, with the nopaline synthase terminator sequence used in both expression cassettes. Then, these two expression cassettes were inserted into the T‐DNA region of the pBI121‐based binary vector to form the transforming vector (Esmaeili et al ., 2019), which was used to transform wild‐type (WT) cotton. A total of 27 independent transgenic cotton plants were generated via Agrobacterium‐mediated transformation method (Bayley et al ., 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, engineering crops that can maintain high yield in marginal environments would be a major break‐through in agricultural production. Recently our proof‐of‐concept study showed that co‐overexpression of AVP1 and OsSIZ1 in Arabidopsis improves multi‐stress tolerance substantially, and transgenic plants produced a significantly higher yield under severe stress conditions (Esmaeili et al ., 2019). In this study, we co‐overexpressed OsSIZ1 and AVP1 in cotton, and we showed that OsSIZ1/AVP1 co‐overexpressing cotton plants demonstrated a far more superior performance than all other control plants under all abiotic stress conditions tested.…”
Section: Introductionmentioning
confidence: 99%
“…8 It is unclear whether different gene expression cassettes produce similar levels of mRNA molecules in the same plant tissue. 9 Individual mRNA molecules can correspond to numerous proteins that interact each other and might not behave similarly in a single plant cell. [10][11][12] Furthermore, multiple proteins participating in the same event may have distinct vulnerabilities to protein degradation over the duration of an experiment.…”
Section: Introductionmentioning
confidence: 99%